Magic Gift 4U / Nabilah Farhah Adnan ... [et al.] - Adnan, Nabilah Farhah; Mustafa Kamal, Putri Nabila; Mohd Azhan, Azhanis Azreen; Norman, Nurul Atikah; Wan Mohamad Zuki, Wan Nur Jannah; Mohd Ghani, Nur Salsabila (2021)
Magic Gift 4u is a company that provide a service surprise gift which a valuable gift box that includes gifts for someone that we love such as family, friends or even lover to express affection, and is an extension of the social needs of a packaging function. We will buy or produce presents by hand for special days or anniversaries. All of this requires the use of lovely packing boxes to convey romance or solemnity. In particularly, put a lovely ribbon on the box, no matter what the gift is, and it will instantly make the gift more beautiful. The handmade, huge, and round bow becomes part of the packaging, giving tension and vitality to the packaging while conveying the gift's quality and value. Besides, appearance of the box and the gift also plays an important role. We not only using the box, but we also offer a bouquet of flower when there is a demand from customer. We also offer a few combos’ that customer can give a variety of gift to their loves one such as cloths, necklace, chocolate, Spotify plague, perfume and many more. Other than that, the price is affordable to all people. Our product is suits both gender whether a man or a woman. Our targeting market is for someone that wanted to give a present to someone they love but in surprise way. Magic Gift 4u is suit and open to all race, ethnic, region. Our surprise gift box suitable in any important event such as Mother’s Day, Father’s Day, Birthday, Anniversary and so on. Then, it has already been observed by our group that in Malaysia we do not handle so much about surprise service where the demand for surprise is very high in the market now. We also provide an agent for different state, due to that customer can easily reach the agent based on their location. We are also available in online and offline. We can be found in a social media platform by searching our company name. In addition, people are now lazy to go out looking for gift and that is the reason Magic Gift 4u is established. At the same time, our company provide a services surprise gift box different from the others and we emphasize the quality of the service more than the price of surprise gift which our goals are customer satisfy and happy. It is because it helps company to growth more and can help company to increase our sales. Due to that we will achieve our company goals. Lastly, on this assignment our team which is Magic Gift 4u company or our groupmates wanted to present our business proposal which focus on key points or findings about how we want to start and manage of this business by using business model canvas before being operated. The business model canvas that we will focus on is customer segment, values propositions, channels, customer relationship, revenue streams, key resources, key partnerships, and cost structure.